2019
DOI: 10.20546/ijcmas.2019.801.283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post Harvest Treatments on the Shelf life and Quality of Guava [Psidium guajava (L.)] cv. Allahabad Safeda

Abstract: An experiment was conducted to determine the effect of different post harvest treatments on the shelf life and quality of guava. Different chemicals such as Gibberellic acid, Calcium chloride, Salicylic acid and Potassium permanganate were used, individually and in combinations. The different concentrations of GA 3 at 25 and 50 ppm and combination with KMnO 4 (5g/kg sachet), CaCl 2 at 1 and 2% and in combination with KMnO 4 (5g/kg sachet) and Salicylic acid at 70 & 140 ppm and in combination with KMnO 4 (5g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…Generally, data showed that fruit treated with AS or SA, delayed loss in fruit weight, redundancy in acidity and V.C and decreased the rise of SSC and softening during the storage period, which means delayed decay and improved fruit quality. These finding are in agreement with Islam et al (2018) and Tabasum et al (2019).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, data showed that fruit treated with AS or SA, delayed loss in fruit weight, redundancy in acidity and V.C and decreased the rise of SSC and softening during the storage period, which means delayed decay and improved fruit quality. These finding are in agreement with Islam et al (2018) and Tabasum et al (2019).…”
Section: Discussionsupporting
confidence: 92%